2022
DOI: 10.33594/000000556
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Galectin-3 Exacerbates Age-Related Myocardial Hypertrophy and Fibrosis in Mice

Abstract: Background/Aims: Aging is accompanied by progressive and adverse cardiac remodeling characterized by myocardial hypertrophy, fibrosis, and dysfunction. We previously reported that galectin-3 (Gal-3) is a critical regulator of inflammation and fibrosis associated with hypertensive heart disease and myocardial infarction. Nevertheless, the role and mechanism of Gal-3 in age-related cardiac remodeling have not been previously investigated. We hypothesized that Gal-3 plays a critical role in cardiac aging and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recent studies showed that the absence of Gal-3 in aged mice exacerbates kidney fibrosis, oxidative stress, and promotes renal dysfunction, suggesting that Gal-3 may be protective for kidney aging ( Iacobini et al, 2005 ). We recently studied the cardiovascular phenotype of aged Gal-3 KO mice ( Fontana Estevez et al, 2022 ). At 2 years old, Gal-3 KO mice showed a significantly decreased in survival.…”
Section: Galectin-3 In Cardiac Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that the absence of Gal-3 in aged mice exacerbates kidney fibrosis, oxidative stress, and promotes renal dysfunction, suggesting that Gal-3 may be protective for kidney aging ( Iacobini et al, 2005 ). We recently studied the cardiovascular phenotype of aged Gal-3 KO mice ( Fontana Estevez et al, 2022 ). At 2 years old, Gal-3 KO mice showed a significantly decreased in survival.…”
Section: Galectin-3 In Cardiac Agingmentioning
confidence: 99%
“…It is now well-established that Gal-3 plays a pivotal role in the development and progression of cardiovascular diseases, including heart failure (de Boer et al, 2018), atherosclerosis (Pusuroglu et al, 2017), hypertension (Gonzalez et al, 2014), myocarditis (Souza et al, 2017a;Kovacevic et al, 2018), and ischemic heart disease (Wan et al, 2022;Wang et al, 2023). Furthermore, recent findings emphasize the significant contribution of Gal-3 to the temporal evolution of cardiac and renal aging, suggesting a key role in the mechanisms associated with organ senescence (Iacobini et al, 2005;Fontana Estevez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H19 acts as an inhibitor of competitive endogenous RNA (ceRNA) by secreting microRNA-19a (miR-19a) to regulate cytokine signaling expression, which subsequently leads to cardiac senescence by stimulating the p53/p21 signaling pathway, while H19 knockdown inhibits cardiomyocyte senescence [ 42 ]. Gal-3 is closely related to the regulation of cardiac remodeling, and the decreased expression of Gal-3 gene in the process of aging can aggravate cardiac hypertrophy, fibrosis and apoptosis, increase the expression of Ang II, matrix metalloproteinase-9 (MMP-9) and transforming growth factor (TGF- ), but decrease the expression of SIRT1 and sirtuin-7 (SIRT7) [ 43 ]. Ubiquitin endonuclease activity is also associated with age-related changes in the heart because genes involved in ubiquitin transfer are transcriptional up-regulated with age, which contributes to the induction of cardiomyocyte autophagy.…”
Section: Changes In Gene Regulation and Metabolism In Senescent Card...mentioning
confidence: 99%